Assessing Environmental Enteric Dysfunction via Multiplex Assay and its Relation to Infant Growth Among HIV-Exposed Infants in Dar es Salaam, Tanzania. (14th June 2022) - Lauer, Jacqueline; Kirby, Miles; Muhihi, Alfa; Ulenga, Nzovu; Aboud, Said; Liu, Enju; Choy, Robert K.M; Kou, Jianqun; Gewirtz, Andrew; Fawzi, Wafaie; Sudfeld, Christopher; Manji, Karim; et al.
Abstract: Objectives: Environmental enteric dysfunction (EED), a subclinical state of intestinal inflammation, may contribute to poor growth in children in low-resource settings, but validated biomarkers are lacking. Multiplex assays, such as the 11-plex Micronutrient and EED Assessment Tool (MEEDAT), hold promise due to their ability to capture multiple domains of EED; however, MEEDAT's ability to predict poor growth has not been well established. We sought to examine the relationship between markers of EED and growth among HIV-exposed infants in Dar es Salaam, Tanzania. Methods: We performed a sub-study of 467 infants of HIV-infected mothers who participated in a randomized, double-blind, placebo-controlled trial assessing the effect of vitamin D3 supplementation during pregnancy. Infant serum samples collected at 6 weeks and 6 months were analyzed for anti-flagellin and anti-LPS IgA and IgG via ELISA as well as MEEDAT, which incorporates two markers of EED [fatty acid-binding protein (I-FABP) and soluble CD14 (sCD14)]. Biomarkers were categorized into quartiles for primary analyses and as continuous exposures for exploratory analyses. Associations with subsequent growth outcomes [length-for-age Z-score (LAZ), weight-for-length Z-score (WLZ), and weight-for-age Z-score (WAZ)] at 12 months of age were assessed using linear regression. Results: At 12 months, nearly half (∼46%) of infants were stunted (LAZ <-2), and ∼3% were wasted (WLZ <-2). Higher concentrations of anti-LPS IgG at 6 months were significantly associated with lower LAZ at 12 months (ptrend  = 0.034). In continuous analyses, higher concentrations of anti-flagellin IgA at 6 weeks were significantly associated with lower LAZ at 12 months (β: −0.46, 95% CI: −0.82, −0.11) as were anti-LPS IgA (β: −0.28, 95% CI: −0.53, −0.03) and anti-LPS IgG (β: −0.24, 95% CI: −0.48, −0.01) at 6 months. Higher concentrations of anti-flagellin IgA and anti-LPS IgA at 6 months were significantly associated with lower WAZ at 12 months (β: −0.34, 95% CI: −0.61, −0.07; β: −0.24, 95% CI: −0.44, −0.04). No significant associations were observed between I-FABP or sCD14 and infant growth at 12 months. Conclusions: Unlike anti-flagellin and anti-LPS Igs, MEEDAT's biomarkers of EED, I-FABP and sCD14, were not associated with subsequent growth among HIV-exposed infants in Tanzania. Funding Sources: NIDDK and NICHD.